Auditing Fee Determinants for Different Industries in Shanghai Stock Exchange - lin, shangyi (2011)
Since 2001, China's Securities Regulatory Commission began to require every public company to disclose auditing fee in Chinese stock exchange. This research use auditing fee in Shanghai stock exchange to find determinants for auditing fee in different industries of Shanghai stock exchange. In this research, I find determinates in different industries. Previous researchers only used one or two year data of stock market. Owing to accuracy of results, I will use five year of data of Shanghai stock exchange. I will use panel data to obtain result, whereas other researchers usually used regression. Additionally, two new ratios are employed to substitute for variables. Software in this research is Stata11. Most of results in this dissertation are consistent with previous industry. There are some new findings in Shanghai stock exchange. Based on results, auditor’s size is the significant variable in 90% of industries. Besides auditor’ size, auditee’s size is another common variable to determine auditing fee in most of industries. However, auditee’s profitability’s results are not consistent with previous studies. Thought this variable is still significant in many industries, coefficients of auditee’s profit are opposite with expectation.